2008
DOI: 10.1080/09674845.2008.11732803
|View full text |Cite
|
Sign up to set email alerts
|

First detection of a class 2 integron among clinical isolates of Serratia marcescens

Abstract: Serratia marcescens is a frequent nosocomial isolate and is associated with a variety of clinical sources, including blood, urine and sputum, and can cause significant infection. Infections can be difficult to treat due to its resistance to a variety of antimicrobial agents. An investigation of a population of 30 clinical strains revealed the presence of a class 2 integron among nine of the isolates, which represents the first isolation of this integron in Serratia species. This integron contained the gene cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Some genes encoding QAC resistance may be found on large, transmissible plasmids (resistance plasmids) carrying determinants on integrons conferring resistance to different antimicrobials and QACs [68,[89][90][91]. For example, in Enterobacteriaceae, a class 1 integron was identified that carried qacE, qacF, qacG and qacH [63] in association with other antibiotic resistance genes.…”
Section: Co-resistance and Cross-resistance To Quaternary Ammonium Comentioning
confidence: 98%
“…Some genes encoding QAC resistance may be found on large, transmissible plasmids (resistance plasmids) carrying determinants on integrons conferring resistance to different antimicrobials and QACs [68,[89][90][91]. For example, in Enterobacteriaceae, a class 1 integron was identified that carried qacE, qacF, qacG and qacH [63] in association with other antibiotic resistance genes.…”
Section: Co-resistance and Cross-resistance To Quaternary Ammonium Comentioning
confidence: 98%
“…In Serratia marcescens, 9 out of 30 (30.0%) were positive for class 2 integron, with identical dfrA1-sat1-aadA1 cassette arrays (Crowley, 2008). Also, class 2 integron had been occasionally reported in Pasteurella aerogenes (One porcine Pasteurella aerogenes strain 343) (Schwarz et al, 2010).…”
Section: Class 2 Integronmentioning
confidence: 99%
“…In Canada, 6 out of 54 strains of Salmonella spp. isolated from healthy swine contained class 2 integron with dfrA1-sat1-aadA1 cassette arrays (Crowley, 2008;San Martin et al, 2008). In Japan, 94 Salmonella strains isolated from animals were characterized for antibiotic resistance, of which 4 (4.3%) isolates of S. Enteritidis sampled from poultry were found to contain class 2 integron with arrays of estX-sat2-aadA1 (Ahmed et al, 2009).…”
Section: Class 2 Integronmentioning
confidence: 99%
“…marcescens is also known as an opportunistic pathogen which is responsible for an increasing number of serious nosocomial infections and colonization of hospital wards [9]. Antibiotic resistance in S. marcescens is coded by genes which often located in plasmids and integrons [10]. The purpose of this study was to characterize mobile genetic elements of a causative agent of onion decay isolated in South of Ukraine.…”
mentioning
confidence: 99%
“…PCR development. Primers a79F and a79R [13], and primers YV1 and YV4, which were designed from the 16S rRNA gene region of the S. marcescens genome [14], pA and pH described by [10] were used in a PCR. Bacteria grown in broth were washed once with 0.5 M NaCl, re-suspended in distilled water, and 1 ml suspension was used as a template.…”
mentioning
confidence: 99%